1981
DOI: 10.1104/pp.68.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Seagrass Photosynthesis by Ultraviolet-B Radiation

Abstract: Effects of ultraviolet-B radiation on the photosynthesis of seagrasses (Halophilaengebnami Aschers, Haloukl wrightii Aschers, and Syringodium fihforme Kutz) were examined. The intrinsic tolerance of each seagrass to ultraviolet-B, the presence and effectiveness of photorepair mechanisms to ultraviolet-B-induced photosynthetic inhibition, and the role of epiphytic growth as a shield from ultraviolet-B were investigated.Hakdad was found to possess the greatest photosynthetic tolerance for ultraviolet-B. Photosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 20 publications
1
33
0
1
Order By: Relevance
“…The failure of reciprocity has been observed in Chlorella pyrenoidosa for the inhibition of photosynthesis by UV-C radiation (254 nm; Redford and Myers 1951) and for UV-B induced photoinhibition of photosynthesis in the seagrass Halodule wrightii (Trocine et al 1981). …”
Section: Photoinhibition Vs Dose and Dosage Ratementioning
confidence: 97%
“…The failure of reciprocity has been observed in Chlorella pyrenoidosa for the inhibition of photosynthesis by UV-C radiation (254 nm; Redford and Myers 1951) and for UV-B induced photoinhibition of photosynthesis in the seagrass Halodule wrightii (Trocine et al 1981). …”
Section: Photoinhibition Vs Dose and Dosage Ratementioning
confidence: 97%
“…Flavonoids are believed to protect these plants against UV radiation (e.g. Trocine et al 1981). Additionally, accumulation of phenolics has been correlated with reduced microbial growth (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Often, reciprocity is assumed to hold (Damkaer et al 1981;Smith and Baker 1982) or its importance is acknowledged (Béland et al 1999;Kouwenberg et al 1999) though it is not directly tested. Trocine et al (1981) found that at a given UV-B dose, low dose rates over a long period of time produced the same degree of photosynthetic inhibition as higher dose rates over a shorter period of time in two of three species of seagrasses. Reciprocity held, and no significant PER was found in these two species.…”
mentioning
confidence: 99%